Outcomes of Transcatheter Aortic Valve Replacement in Transplant Recipients. Issue 4 (3rd July 2020) - Chahine, Johnny; Gajulapalli, Rama D.; Kadri, Amer N.; Sammour, Yasser; Puri, Rishi; Reed, Grant W.; Krishnaswamy, Amar; Perez, Oscar; Lak, Hassan; Chawla, Sanchit; Gad, Mohamed M.; Yun, James; et al.
ABSTRACT: Background: Transcatheter aortic valve replacement (TAVR) has become the mainstay in the treatment of patients with severe calcific aortic stenosis. However, little is known about the outcomes of TAVR in transplant recipients. Methods: Patients who underwent TAVR and transplant were compared to a control group of TAVR patients who did not have a transplant, between 2014 and 2017. The primary endpoints were all-cause mortality and the onset of prosthetic valve endocarditis. The secondary endpoints were based on the Valve Academic Research Consortium-2 (VARC-2) criteria. Propensity score matching, based on age, race, and gender, was used to compare the outcomes between transplant and non-transplant patients. Results: 35 patients underwent TAVR as well as organ transplants (26 solid organ and 9 bone marrow). Compared to non-transplant patients (n = 1, 366), transplant patients underwent TAVR at a younger age. After matching, transplant patients (n = 34) were more likely to develop prosthetic valve endocarditis compared to non-transplant patients (n = 68) ( p = 0.04); however, the majority were on immunosuppressive agents. Transplant patients had a higher 3-year mortality rate, but not 30-day and 1-year mortality ( p < 0.001). NYHA after TAVR was also higher in transplant patients ( p = 0.04). There was no significant difference in other outcomes based on VARC-2 criteria. Conclusion: Transplant patients undergo TAVR at a younger age, yet are at an increased risk of post-TAVR complications. In transplant patients, survival is similar to non-transplant patients at 30 days and 1-year. TAVR is a viable treatment option for patients with organ transplantation and severe symptomatic aortic stenosis. Abbreviations: AR: Aortic Regurgitation; AS: Aortic Stenosis; AVR: Aortic Valve Replacement; CHF: congestive heart failure; IQR: Interquartile Ranges; NYHA: New York Heart Association; PVR: Paravalvular Regurgitation; TAVR: Transcatheter Aortic Valve Replacement; VARC: Valve Academic Research Consortium